Nursing Intervention for Caregivers of Post Autologous Bone Marrow Transplantation Patients at Home - Asmaa Farouk Mohamed¹, Nawal Soliman², Hemat Abd-El-Moneem El-Sayied³, Asmaa Talaat4 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Autologous bone marrow transplantation is a curative procedure for hematological diseasesand immune deficiencies. The unique and intensive nature of this treatment requires distinctive care duringand post the entire transplant course. Nursing intervention for caregivers post autologous bone marrowtransplantation patients at home is an important component of the care that improves and develops knowledgeand practice of the caregivers, to take care of the patients in order to help them follow the demandingtreatment plan to reach recovery. Aim to evaluate the effect of nursing intervention for caregivers of postautologous bone marrow transplantation patients at home. Material and Method: A Quasi-experimentalstudy was carried out among convenient sample of 143 patients and their caregivers who attended the followup clinic during the first six months post autologous bone marrow transplantation. The study was conductedamong patients and their caregivers in three different hospitals Sheikh Zayed Specialized Hospital, Nationaloncology institute, and Nasser institute at outpatient’s follow-up clinics. A self-administered questionnaireof patients and their caregivers’ demographic data, and reported checklist of caregivers’ knowledge andpractices toward post-autologous bone marrow transplantation patients at home. Results: there was astatistically significant difference between pre and post nursing intervention, which indicate improvement incaregivers’ knowledge and practice post implementation of the nursing intervention program, and positivecorrelation between their knowledge and practice. Conclusion and Recommendations: Although caregivershad adequate knowledge, practice on some aspects, gaps were identified. There is a need for educationalinterventions and discharge plan to upgrade knowledge and practices of the caregivers of post autologousbone marrow transplantation patient at home.